Re-Contextualizing Vocational Didactics in Norwegian Vocational Education and Training - Nore, Hæge (International Journal for Research in Vocational Education and Training, 2015)
This article explores teachers and trainers didactical practices in different contexts in Norwegian VET: schools and workplaces. With the introduction of e-resources and e-portfolios in VET, learners as well as teachers and trainers experience a more hybrid learning-arena, which claims for a recontextualization of vocational didactics as well as re-defining roles and responsibilities of the actors. The article discuss new forms of boundary crossing, dealing with e-portfolios as boundary objects, increasing learner autonomy, transformative learning outcomes, interaction between actors and designing learning processes in hybrid learning-arenas. Vocational didactics as understood in a teacher-training context are challenged by more actors and new forms of interactivity with technological tools crossing sites. The study is based on a longitudinal study in a national project on quality assessment, interviews with teachers and trainers as well as apprenticeship training offices supported by documentary evidence from three trades: sales, plumbing and industrial mechanics.